Moral Authenticity in a Turbulent Age: Charles Taylor and the Diary of Etty Hillesum - Lalonde, Marc P. (Studies in religion, 2019)
This paper explores the relation between the moral philosophy of Charles Taylor and the wartime diary of Etty Hillesum. Written in Amsterdam between 1941 and 1942, Hillesum's diary records her effort to construct a meaningful identity in relation to the Nazi occupation of the Netherlands. That effort, I want to claim, is clarified via an interface with Taylor's notion of "authenticity." Taylor argues that authenticity constitutes a moral ideal that serves to measure the worth and value of the lived life. Such is the fundamental mission of Hillesum. In the final analysis I argue that Taylor's moral philosophy lends structure, form and substance to Hillesum's thought, while Hillesum's journey vivifies the veracity of Taylor's project. Her life situation both embodies and expresses the contemporaneity of Taylor's work and illuminates its existential significance. Thus the importance of authenticity is not just a philosophical hypothesis but an issue with historical flesh and bone. Or so suggests Hillesum's search for authenticity in a turbulent age.